Bacterial colonisation of leg ulcers and its effect on the success rate of skin grafting. - Gilliland, E. L. (Royal College of Surgeons of England, 1988)
There is little information on the immediate and long-term results of skin grafting to chronic lower limb ulcers. Our experience in their management had led us to analyse, retrospectively, the results of split thickness skin grafts applied to lower limb ulcers in 88 consecutive patients. Graft take has been related to bacterial growth from ulcer swabs taken on admission, preoperatively and postoperatively. Follow-up was for a median of 18 months. Initial graft take varied from 20% to 100% (median 85%). Bacterial flora grown from the ulcer swabs varied with the duration of the ulcer and the treatment. Analysis by bacterial type has shown that Staphylococcus aurcus and Pseudomonas significantly reduced skin graft healing. Overall, 90% of these ulcers had healed with a median of 6 weeks' in-patient treatment. Examination of the swab results from the 8 ulcers that were slow to heal postoperatively and the 8 ulcers that recurred 6 days to 8 months after discharge from hospital revealed that 15 out of 16 (94%) grew S. aurcus; none had Pseudomonas isolated from them. After eighteen months 8% of these ulcers remain active. Aetiology appears important as this figure is 6% for limbs affected by venous disease only, 13.3% for limbs with arterial disease only and 13.6% for limbs with both venous and arterial disease.